2014
DOI: 10.1136/annrheumdis-2014-205508
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells have a proinflammatory role in the pathogenesis of autoimmune arthritis

Abstract: Objectives Although myeloid-derived suppressive cells (MDSCs) have been linked to T-cell tolerance, their role in autoimmune rheumatoid arthritis (RA) remains elusive. Here we investigate the potential association of MDSCs with the disease pathogenesis using a preclinical model of RA and specimen collected from RA patients. Methods The frequency of MDSCs in blood, lymphoid tissues, inflamed paws, or synovial fluid and their association with disease severity, tissue inflammation, and the levels of pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
150
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 35 publications
9
150
2
2
Order By: Relevance
“…Tregs can suppress autoimmune process and maintain peripheral tolerance 24 . A recent paper by Guo et al showed that MDSCs obtained from CIA mice promoted Th17 differentiation in a IL-1 dependent manner and therefore have a proinflammaotory role in the pathogenesis of inflammatory arthritis 19 , which is different from our results. Such discrepancy in the results about the role of MDSCs in various effector CD4+ T cell populations might be due to the context-dependent interaction between MDSCs and different subsets of CD4+ T cells.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Tregs can suppress autoimmune process and maintain peripheral tolerance 24 . A recent paper by Guo et al showed that MDSCs obtained from CIA mice promoted Th17 differentiation in a IL-1 dependent manner and therefore have a proinflammaotory role in the pathogenesis of inflammatory arthritis 19 , which is different from our results. Such discrepancy in the results about the role of MDSCs in various effector CD4+ T cell populations might be due to the context-dependent interaction between MDSCs and different subsets of CD4+ T cells.…”
Section: Discussioncontrasting
confidence: 57%
“…Given the potent immuoregulatory activity of MDSCs, it could be expected that MDSCs could have therapeutic impact on RA. There have been discordant results regarding the effect of MDSCs on RA [12][13][14][15][16][17][18][19] . However, all the previous papers performed adoptive transfer of MDSCs in animal model of RA to verify whether the MDSCs had therapeutic effects on RA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Strikingly, female patients with SLE showed a higher frequency of MDSCs in PBMCs than male patients. Although transplantation of MDSCs can improve the condition of several autoimmune diseases in animal models, several recently published studies have shown that MDSCs play a proinflammatory role in the pathogenesis of EAE and RA by promoting T helper 17 cell differentiation [29][30][31]. Notably, CD11b + Gr-1 + MDSCs are a complex mixture of myeloid phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The protective role of MDSCs against inflammation and autoimmunity has been widely observed in various pathophysiological conditions [26][27][28]. However, several recent studies have shown that MDSCs play a proinflammatory role in the pathogenesis of experimental allergic encephalitis (EAE) and rheumatoid arthritis (RA) by promoting Th17 cells differentiation [29][30][31], suggesting that the roles of MDSCs in inflammatory and autoimmune diseases remain controversial.…”
Section: Introductionmentioning
confidence: 99%